Transdermal delivery of isoniazid and rifampin in guinea pigs by electro-phonophoresis. (1st January 2017) - Chen, Suting; Han, Yi; Yu, Daping; Huo, Fengmin; Wang, Fen; Li, Yunxu; Dong, Lingling; Liu, Zhidong; Huang, Hairong
Abstract: Electro-phonophoresis (EP) has been used as a drug delivery approach in clinical fields. The objective of the present study is to evaluate the skin permeability of isoniazid and rifampin in guinea pigs by EP to provide reference basis for clinical applications of such transdermal delivery system in the treatment of patients with superficial tuberculosis. Isoniazid and rifampin solutions were delivered transdermally with or without EP in health guinea pigs for 0.5 h. Local skin and blood samples were collected serially at 0, 1/2, 1, 2, 4, 6 and 24 h after dosing. Drug concentrations in local skin and blood were evaluated by high-performance liquid chromatography. Isoniazid concentrations in local skin of guinea pigs receiving isoniazid through EP transdermal delivery were significantly higher than in animals receiving only isoniazid with transdermal patch. However, for rifampin, patches alone group presented almost uniform concentration versus time curve with that of EP group, and both groups had concentrations much higher than the therapeutic concentration of the drug over sustainable time. After EP transdermal delivery, the mean peak concentrations of isoniazid and rifampin in skin were 771.0 ± 163.4 μg/mL and 81.2 ± 17.3 μg/mL respectively. Neither isoniazid nor rifampin concentration in blood could be detected (below the lower detection limit of 1 μg/mL) at any time point. The present study showed that application of EP significantly enhanced INH penetration through skin in guinea pigs, while RIF patch alone obtained therapeutic concentration in local skin. Our work suggests several possible medication approaches for efficient treatment of superficial tuberculosis.